2013
DOI: 10.1093/pcp/pcs181
|View full text |Cite
|
Sign up to set email alerts
|

FT-Like NFT1 Gene May Play a Role in Flower Transition Induced by Heat Accumulation in Narcissus tazetta var. chinensis

Abstract: The low-temperature flowering-response pathway, used as an inductive stimulus to induce flowering in plant species from temperate regions in response to cold temperature, has been extensively studied. However, limited information is available on the flower transition of several bulbous species, which require high temperature for flower differentiation. Narcissus tazetta var. chinensis (Chinese narcissus) exhibits a 2 year juvenile phase, and flower initiation within its bulbs occurs during summer dormancy. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…chinensis, known as NFT1, act as a flowering time regulator when ectopically and constitutively expressed in ft-3 mutant Arabidopsis plants. In these transgenic lines, SOC1 a target of FT showed to be up-regulated as expected based on FT functioning in Arabidopsis (Li et al, 2013).…”
Section: Gene Function Verification Using Model Speciessupporting
confidence: 67%
See 1 more Smart Citation
“…chinensis, known as NFT1, act as a flowering time regulator when ectopically and constitutively expressed in ft-3 mutant Arabidopsis plants. In these transgenic lines, SOC1 a target of FT showed to be up-regulated as expected based on FT functioning in Arabidopsis (Li et al, 2013).…”
Section: Gene Function Verification Using Model Speciessupporting
confidence: 67%
“…Despite that these technologies are already available for thirty years and have undergone various improvements over the last decades, it is still far from trivial to transform any desired plant species. Therefore, it is still common practise to perform gene function verifications by overexpression or complementation studies using a model species as target (cross-species analysis) (Li et al, 2013, Tsaftaris et al, 2012.…”
Section: Verification Of Gene Functionmentioning
confidence: 99%
“…Numerous studies have concluded, FT orthologs possessing floral inductive function in woody perennials (Hisada et al, 1997; Endo et al, 2005; Böhlenius et al, 2006; Hsu et al, 2006; Carmona et al, 2007; Kotoda et al, 2010; Song et al, 2013); grasses (Yan et al, 2006; Tamaki et al, 2007; Kikuchi et al, 2009; Meng et al, 2011; Wu et al, 2013; Coelho et al, 2014); legumes (Kong et al, 2010; Ono et al, 2010; Hecht et al, 2011; Laurie et al, 2011); ornamental (Hayama et al, 2007; Hou and Yang, 2009; Imamura et al, 2011), CsFTL3 from chrysanthemum ( Chrysanthemum seticuspe ; Oda et al, 2012; Xiang et al, 2012; Li et al, 2013); and others such as BvFT2 from sugar beet ( Beta vulgaris ; Pin et al, 2010), NtFT4 from tobacco ( Nicotiana tabacum ; Harig et al, 2012), StSP3D form potato ( Solanum tuberosum ; Navarro et al, 2011), AcFT2 from onion ( Allium cepa ; Lee et al, 2013), PaFT from avocado ( Persa americana ; Ziv et al, 2014), LsFT from lettuce ( Lactuca sativa ; Fukuda et al, 2011; Above information was listed in Supplementary Table S1). Previously study suggests a conserved ancestral function of FT -like proteins in transmitting inductive signals in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Limited information is available on the flower transition of bulbous species, which require high temperature for flower differentiation in species such as saffron. The results obtained by Li et al 137 working on Narcissus tazetta, a bulbous species that requires high temperature for flower differentiation, showed that Narcissus FLOWERING LOCUS T1 (NFT1) transcripts were abundant during flower initiation in mature bulbs and were up-regulated by high temperature, suggesting that NFT1 possibly takes part in flower transition control in response to this factor. Given the similarities in the floral induction process of saffron and narcissus, the same upregulation of FT by high temperature could be expected to happen in saffron, although this needs to be confirmed.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%